The national birth defects prevention study: A review of the methods. Issue 8 (2nd June 2015) - Reefhuis, Jennita; Gilboa, Suzanne M.; Anderka, Marlene; Browne, Marilyn L.; Feldkamp, Marcia L.; Hobbs, Charlotte A.; Jenkins, Mary M.; Langlois, Peter H.; Newsome, Kimberly B.; Olshan, Andrew F.; Romitti, Paul A.; Shapira, Stuart K.; et al.
Abstract : Background: The National Birth Defects Prevention Study (NBDPS) is a large population‐based multicenter case–control study of major birth defects in the United States. Methods: Data collection took place from 1998 through 2013 on pregnancies ending between October 1997 and December 2011. Cases could be live born, stillborn, or induced terminations, and were identified from birth defects surveillance programs in Arkansas, California, Georgia, Iowa, Massachusetts, New Jersey, New York, North Carolina, Texas, and Utah. Controls were live born infants without major birth defects identified from the same geographical regions and time periods as cases by means of either vital records or birth hospitals. Computer‐assisted telephone interviews were completed with women between 6 weeks and 24 months after the estimated date of delivery. After completion of interviews, families received buccal cell collection kits for the mother, father, and infant (if living). Results: There were 47, 832 eligible cases and 18, 272 eligible controls. Among these, 32, 187 (67%) and 11, 814 (65%), respectively, provided interview information about their pregnancies. Buccal cell collection kits with a cytobrush for at least one family member were returned by 19, 065 case and 6, 211 control families (65% and 59% of those who were sent a kit). More than 500 projects have been proposed by the collaborators and over 200 manuscripts published using data from the NBDPS through December 2014. Conclusion: The NBDPS has made substantial contributions to the field of birth defects epidemiology through its rigorous design, including case classification, detailed questionnaire and specimen collection, large study population, and collaborative activities across Centers. Birth Defects Research (Part A) 103:656–669, 2015. © 2015 Wiley Periodicals, Inc.